American vs. British Voting Systems: Comparative Study - Boucif, Ben ali, I EL-Khansa Khaoula (University of El-oued, 2021)
The aim of the current study is to explain the structure of the political system and the process of election in the United States of America (USA) and the United Kingdom (UK), and to examine the similarities and differences between them. The UK and the USA are known for their interesting political structures which are considered to be sophisticated. Elections in both sides of the equation are the pillars of their strength and authority over the world. Britain at the first hand, is a parliamentary democracy under the umbrella of a constitutional monarchy system. In Britain, the Monarch who belongs to the English church serves as the head of the nation; while the real authority is in the hand of the parliament. The role of the monarch is merely ceremonial; it undertakes constitutional and representational duties. It cannot make or pass legislations but to represent the nation in international forums. America in the other hand is Federal Constitutional Republic. In America, the highest authority belongs to the president and the congress who works separately from the executive and judiciary. The president in America serves as the head of the head of and state and the head of government; He is elected through a process called "Electoral College". The method adopted to conduct this research and achieve its objectives is descriptive analytical that depends on a qualitative research since it is based on colleting data via reviewing book, articles and surfing websites; meanwhile, it attempts to analyze and interpret constitutions` clauses that are associated with the political and electoral systems in both countries. The study intends to describe the political and electoral system of the USA and the UK and depicts the differences and similarities between them. The findings of the study revealed that the United Kingdom and the United States of America share numerous common features as well as distinctive ones in terms of political and electoral systems.
Keywords: American political system, American voting system, British political system, British voting system, Election.